Factors contributing to pregnancy amongst female students at the University of Limpopo, Turfloop campus, South Africa - Tladi, F. M.; Jali, N. M. (My University, 2014)
From observation, unwanted pregnancy among students at some of South African universities is fast becoming a problem. Inspite of the availability of contraceptives at the students health centre of the University of Limpopo, Turfloop campus, and the provision of free condoms at the halls of residences. The aim of this study was to examine the factors which contribute to pregnancy amongst the University of Limpopo students. A quantitative research study was conducted among 19 University of Limpopo female students in order to examine the factors that contribute to them becoming pregnant. A structured questionnaire with close ended questions was used to collect data from the 19 students who participated in this study. The questionnaire was divided into Section A which was on demographic data, Section B on the personal data and Section C on the sexuality data. Descriptive statistics were used to describe and summarise the data. In contrast to the problem statement that the University of Limpopo could be experiencing a high pregnancy rate among students, the findings indicated that the pregnancy rate was not as high as was suspected. Sexuality education specifically for adolescents is imperative for all junior and secondary school pupils. Contraceptive use awareness campaigns have to be more rigorous and intensified.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) Supplement 1:2 (June), 2014, pp. 275-283.
Keywords: Pregnancy; Contraceptives; University female students; Pregnancy, unwanted -- South Africa